Molecular epidemiology of Blastocystis isolated from Malaysia and Libya / Awatif Mohamed Abdulsalam - Awatif Mohamed, Abdulsalam (2013)
Blastocystis is a common intestinal parasite infecting humans and different animal species. The purpose of this study was to investigate the molecular epidemiology of Blastocystis infection in Malaysia and Libya, and to investigate the occurrence of Blastocystis sp. in water sources from Malaysia. Two groups of stool samples were collected from 300 primary schoolchildren in Pahang, Malaysia and 380 outpatients attending the Central Laboratory in Sebha, Libya. While for water, a total of 65 samples were collected from different water sources in the study areas of Pahang, Malaysia. The stools and water samples were processed accordingly and were subjected to in vitro cultivation in Jones’ medium followed by PCR, cloning, sequencing. The DNA sequences were phylogenetically analyzed using the neighbor-joining method. The questionnaire data of demographic, socio-economic, environmental and personal hygiene factors associated with intestinal parasitic infections were also analyzed. In Malaysia, the overall prevalence of Blastocystis infection among rural primary schoolchildren was 25·7%. Univariate and multivariate analyses showed that the absence of a piped water supply (OR = 3·13; 95% P < 0·001) and low levels of mothers’ education (OR = 3·41; P < 0·01) were the significant predictors of Blastocystis infection. Phylogenetic analysis revealed that Blastocystis isolates were classified into three distinct subtypes (ST); ST3 (39.4%) followed by ST1 (36.4%) and ST2 (18.2%) while 6.0% of the isolates were mixed subtype infections. ST1 was more common among schoolchildren aged 10 years (P = 0.012), those who lack piped water supply (P = 0.026) and toilet facility (P = 0.037) in their households. While ST3 infection was more common among schoolchildren aged >10 years (P = 0.042). As for water samples, it was found to be 92.3% (60/65) were contaminated with Blastocystis species. These were 32.3% in river water, 27.7% tap water, 16.9% rain iv water storage and 15.4% wells. The most predominant Blastocystis subtype was ST4 (80.4%) followed by ST1 (19.6%). Nucleotide sequences of Blastocystis ST1 from water samples were 100% identical to that of Blastocystis found in schoolchildren providing molecular-based evidence supporting waterborne potential of Blastocystis. While in Libya, the overall prevalence of Blastocystis infection among outpatients was 22.1%. The prevalence was significantly higher among males (P = 0.036) and patients aged ≥18 years (P < 0.001). Univariate analysis showed significant associations between Blastocystis infection and the occupational status (P = 0.017), family size (P = 0.023) and educational level (P = 0.042). Multivariate analysis confirmed that the age of ≥ 18 years (OR = 5.7; P = 0.001) and occupational status (OR = 2.2; P = 0.045) as significant predictors of Blastocystis infection. The prevalence of gastrointestinal symptoms among Blastocystis-infected patients was higher compared to uninfected patients (P < 0.001). The most common symptoms were abdominal pain (76.4%), flatulence (41.1%) and diarrhea (21.5%). Phylogenetic analysis revealed that Blastocystis isolates were assembled under three subtypes; ST1 (51.1%) followed by ST2 (24.4%), ST3 (17.8%) and mixed subtype infections (6.7%). ST1 infection was significantly associated with female gender (P = 0.009) and educational level (P = 0.034). ST2 was also significantly associated with low level of education (P = 0.008) and ST3 with diarrhoea (P = 0.008).